Stratégies d’intégration et de support en santé mentale des immigrants francophones au Canada anglais. - Archambault, Hélène; de Moissac, Daniel; Tempier, Raymond (Minorités linguistiques et société / Linguistic Minorities and Society, 2024)
Résumé Cet article explore les stratégies d’intégration au système de santé telles que proposées par des personnes immigrantes francophones au sein de communautés francophones en situation minoritaire au Canada (CFSM). Une recherche qualitative par entrevues semi-dirigées a été menée dans trois villes canadiennes auprès de soixante personnes adultes immigrantes ou réfugiées. Centrées sur les représentations des personnes immigrantes quant aux services de soutien en santé mentale, diverses stratégies ont été dégagées. La préparation prémigratoire et le regroupement des informations sous un guichet unique semblent contribuer à une intégration réussie. L’appui des organismes communautaires et des autorités religieuses est bénéfique pour le soutien informationnel et socioémotionnel des nouveaux arrivants, ayant des retombées positives sur leur bien-être et leur capacité de s’intégrer à leur nouveau milieu de vie. Mots-clés : immigration, francophones, intégration, système de santé, stratégies Abstract This article explores healthcare integration strategies proposed by Francophone immigrants within Francophone minority communities (FMCs) in Canada. A qualitative study using semi-structured interviews was conducted in three Canadian cities with sixty adult immigrants and refugees. Focusing on immigrants’ perceptions of mental health support services, various strategies were identified. Pre-migration preparation and centralizing information seem to contribute to successful integration. The support of community organizations and religious authorities is beneficial for the socio-emotional and information support of newcomers, having a positive impact on their well-being and their ability to integrate into their new living environment. Keywords: immigration, Francophones, integration, healthcare, strategies

Expérience d'immigration de Francophones en contexte linguistique minoritaire au Canada : défis et répercussions sur la santé mentale - Archambault, Hélène; de Moissac, Danielle; Levesque, Annabel; Kinkumba, Babou; Gueye, Ndeye Rokhaya; Tempier, Raymond; Alimezelli, Hubert Tote (Reflets, 2021)
Cet article explore les défis rencontrés par de nouveaux arrivants francophones à leur arrivée dans une communauté francophone en situation minoritaire au Canada, les répercussions qui en découlent et les facteurs modérateurs ayant une incidence sur leur intégration. Une recherche qualitative par entrevues semi-dirigées a été menée dans trois villes canadiennes auprès de soixante adultes immigrants ou réfugiés. Le défi principal auquel sont confrontées ces personnes est la barrière linguistique ; elle vient amplifier les défis liés à l’intégration sociale et la recherche de l’emploi. L’expérience migratoire a aussi une répercussion sur la santé mentale, sur les relations avec les proches et sur la santé physique. Le soutien social et la résilience personnelle favorisent l’adaptation dans la communauté d’accueil. Mots-clés : immigration, francophones, intégration, contexte linguistique minoritaire

Barriers to HIV care among Francophone African, Caribbean and Black immigrant people living with HIV in Canada: A protocol for a scoping systematic review - Djiadeu, Pascal; Nguemo, Joseph; Mukandoli, Chantal; Odhiambo, Apondi. J.; Lightfoot, David; Mbuagbaw, Lawrence; Nelson, LaRon. E. (BMJ Open, 2019)
Introduction Language is a social determinant of health. Addressing social determinants of health is paramount to successful progression along the HIV-care continuum. Canada is a bilingual country with French and English as official languages. There are few studies to date that have focused on the impact of being a French-speaking linguistic minority on the HIV-care continuum. The primary objective of this scoping, systematic review of literature is to evaluate existing gaps in access to HIV- care among French-speaking people living with HIV in Canada. Our primary outcome is healthcare services availability and access for French- speaking people living with HIV. Methods and analyses Our scoping, systematic review will draw on a systematic search of published literature, both quantitative and qualitative studies published on French-speaking individuals' healthcare and HIV status in Canada, with particular emphasis on the province of Ontario. We will conduct our search in MEDLINE, the Excerpta Medica Database, the Cumulative Index to Nursing and Allied Health Literature, Web of Science, EBSCO and Google Scholar for work published between 1990 and 2018. Identified articles will be screened in duplicate and full-text articles of relevant studies will be retrieved. Data will also be extracted by two researchers working independently. Any discrepancies that arise will be resolved by consensus or by consulting a third author. Our findings will be reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses. Ethics and dissemination Our proposed research will not be conducted with human participants. We will only use secondary published data and therefore ethics approval is not required. Our findings will be disseminated as peer reviewed manuscripts at conferences and student rounds, and could be of interest to government health agencies and local HIV/AIDS service organisations.

Barriers in accessing HIV care for Francophone African, Caribbean and Black people living with HIV in Canada: A scoping review - Djiadeu, Pascal; Yusuf, Abban; Ongolo-Zogo, Clémence; Nguemo, Joseph; Odhiambo, Apondi J.; Mukandoli, Chantal; Lightfoot, David; Mbuagbaw, Lawrence; Nelson, LaRon. E. (BMJ Open, 2020)
Introduction In 2001, 50%–55% of French-speaking minority communities did not have access to health services in French in Canada. Although Canada is officially a bilingual country, reports indicate that many healthcare services offered in French in Anglophone provinces are insufficient or substandard, leading to healthcare discrepancies among Canada’s minority Francophone communities. Objectives The primary aim of this scoping systematic review was to identify existing gaps in HIV-care delivery to Francophone minorities living with HIV in Canada. Study design Scoping systematic review. Data sources Search for studies published between 1990 and November 2019 reporting on health and healthcare in Francophone populations in Canada. Nine databases were searched, including Medline, Cumulative Index to Nursing and Allied Health Literature, the Cochrane Library, the National Health Service Economic Development Database, Global Health, PsychInfo, PubMed, Scopus and Web of Science. Study selection English or French language studies that include data on French-speaking people with HIV in an Anglophone majority Canadian province. Results The literature search resulted in 294 studies. A total of 230 studies were excluded after duplicates were removed. The full texts of 43 potentially relevant papers were retrieved for evaluation and data extraction. Forty-one studies were further excluded based on failure to meet the inclusion criteria leaving two qualitative studies that met our inclusion criteria. These two studies reported on barriers on access to specialised care by Francophone and highlighted difficulties experienced by healthcare professionals in providing quality healthcare to Francophone patients in Ontario and Manitoba. Conclusion The findings of this scoping systematic review highlight the need for more HIV research on linguistic minority communities and should inform health policymaking and HIV/AIDS community organisations in providing HIV care to Francophone immigrants and Canadians.

Iniquités de santé en milieu minoritaire : diagnostic de la situation chez les immigrants francophones de Sudbury - Hien, Amélie; Lafontant, Jean (Revue canadienne de santé publique / Canadian Journal of Public Health, 2013)
Objectif Cet article vise à mettre au jour des iniquités de santé liées non seulement au fait de vivre dans un milieu linguistique minoritaire, mais aussi au fait d’être immigrant et de vivre dans un nouvel environnement avec une culture d’origine différente de celle de sa communauté d’accueil. Méthode Il s’agit d’une étude qualitative qui présente les expériences personnelles de nombreux immigrants francophones dans leurs rapports aux services et aux soins de santé à Sudbury ainsi que leurs perceptions quant à la qualité et l’accessibilité de ces services et soins. Soixante-douze (72) individus âgés de 18 à 65 ans, dont 45 hommes et 27 femmes, ont participé à cette recherche à travers des entrevues individuelles et des groupes de discussions. Résultats Les résultats obtenus montrent, entre autres, qu’être immigrant et francophone limite l’accès aux services de santé, affecte la qualité de ces services et nuit à une prise en charge efficace des problèmes de santé. C’est ainsi que certains individus ne sont même pas en mesure de donner un consentement éclairé lors de décisions importantes à prendre concernant leur santé. Conclusion L’article fait des suggestions pour que ces immigrants puissent accéder à de meilleurs services et soins de santé, en vue de contribuer à l’amélioration de la santé de la population canadienne dont ils sont partie intégrante.

Vers des services attirants, accessibles et pertinents pour les personnes âgées immigrantes francophones ? - Nduwimana, Mathilde; Home, A. (Reflets, 1995)
Cet article décrit et analyse les besoins et préoccupations des personnes âgées autonomes appartenant aux groupes ethniques francophones et résidant dans Ottawa-Carleton. L'objectif principal est d'explorer les raisons pour lesquelles elles utilisent peu les services de soutien communautaires pour les personnes âgées francophones. Nous avons effectué des entrevues semi-structurées auprès de quatre représentantes et de six personnes âgées des communautés ethno-culturelles francophones, et nous avons effectué une analyse de contenu par thème. Les répondantes ont souligné les besoins de contacts sociaux, d'apprentissage du français et/ou de l'anglais, d'accès aux moyens financiers adéquats et d'information sur les ressources disponibles. Des obstacles liés au contexte socio-écono-politique dans la société d'accueil entravent la satisfaction de ces besoins. La levée de certaines barrières concrètes, la modification des politiques sociales et des pratiques d'intervention faciliteraient l'accès aux services par les personnes âgées des groupes ethniques francophones et augmenteraient leurs options.

Barriers to and enablers of attendance at diabetic retinopathy screening experienced by immigrants to Canada from multiple cultural and linguistic minority groups - van Allen, Zack; Dogba, Maman Joyce.; Brent, Michael. H.; Bach, Catherine; Grimshaw, Jeremy. M.; Ivers, Noah. M.; Wang, Xiaoqin.; McCleary, Nicola.; Asad, Sarah.; Chorghay, Zahraa.; Hakim, Hina; Sutakovic, Olivera; et al. (Diabetic medicine, 2020)
Aim To identify barriers to/enablers of attendance at eye screening among three groups of immigrantsto Canada from cultural/linguistic minority groups living with diabetes. Methods Using a patient-oriented research approach leveraging Diabetes Action Canada's patient engagement platform, we interviewed a purposeful sample of people with type 2 diabetes who had immigrated to Canada from: Pakistan (interviews in Urdu), China (interviews in Mandarin) and French-speaking African and Caribbean nations (interviews in French). We collected and analysed data based on the Theoretical Domains Framework covering key modifiable factors that may operate as barriers to or enablers of attending eye screening. We used directed content analysis to code barrier/enabler domains. Barriers/enablers were mapped to behaviour change techniques to inform future intervention development. Results We interviewed 39 people (13 per group). Many barriers/enablers were consistent across groups, including views about harms caused by screening itself, practical appointment issues including forgetting, screening costs, wait times and making/getting to an appointment, lack of awareness about retinopathy screening, language barriers, and family and clinical support. Group-specific barriers/enablers included a preference to return to one's country of birth for screening, the impact of winter, and preferences for alternative medicine. Conclusion Our results can inform linguistic and culturally competent interventions to support immigrants living with diabetes in attending eye screening to prevent avoidable blindness.

Construction of Francophone families’ health literacy in a linguistic minority situation - Zanchetta, Margareth. Santos; Kaszap, Margot; Mohamed, Mohamed; Racine, Louise; Maheu, Christine; Masny, Diana; Cèsar, Ines; Maltais, Claire; Sangwa-Lugoma, G.; Lussier, Nancy; Kinslikh, Diana (Alterstice, 2012)
With the increase in international mobility, healthcare systems should no longer be ignoring language barriers. In addition to the benefit of reducing long‐term costs, immigrant‐friendly organizations should be concerned with mitigating the way language barriers increase individuals’ social vulnerabilities and inequities in health care and health status. This paper reports the findings of a qualitative, exploratory study of the health literacy of 28 Francophone families living in a linguistic‐minority situation in Canada. Analysis of interviews revealed that participants’ social vulnerability, mainly due to their limited social and informational networks, influenced the construction of family health literacy. Disparities in access to healthcare services could be decreased by having health professionals’ work in alliance with Francophone community groups and by hiring bilingual health professionals. Linguistic isolation and lack of knowledge about local cultural organizations among Francophone immigrants were two important findings of this study.